STUDI ANALISIS FAKTOR FAKTOR YANG MENJADIKAN GURU YANG BAIK - Mahatma, Mahatma (Jurnal Evaluasi Pendidikan, 2021)
Sociologists have long recognized the important role of teachers in education. Teachers have a great influence on shaping a student's personality, knowledge, values, and attitudes towards school. The teacher as a central figure, which in addition to the school climate, academic environment and discipline, is an important element of the school context. Good teachers contribute to the realization of good education. Assessment implies the basic question "What makes a person a good teacher?" The purpose of this study is to examine studies that examine good teachers using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) method. This study focuses on what factors must be possessed to be able to make someone a good teacher. The review of the research literature proved to provide a broad view of the different approaches in terms of personality traits, teaching abilities, professionalism, social emotional abilities and the ability of teachers to realize good education.